Peningkatan Kompetensi Berkomunikasi dalam Pembelajaran Bahasa Inggris melalui Task-Based Learning - Ponikem Ponikem (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objective was to improve the students’ communicative competence through task-based learning in semester II academic year 2016/2017 in the Junior Secondary School 1 Wonosari. A classroom action research was conducted with two cycles at the ninth graders. Data collection techniques used varied, namely, questionnaire, observation, interview, anecdotal records, and document. Data were analyzed descriptively and qualitatively. Results disclose that the students’ communicative competence was improved through task-based learning. Moreover, the students’ comprehension was improved in groups, in unison, in audition as well as in spontaneous communication.